Die verantwoordelikheids-etiek van Max Weber: ’n Toepaslike etiek vir ons tyd? - De Villiers, Etienne (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Max Weber’s ethics with responsibility: a suitable ethics for today? This article provides an interpretation of Max Weber’s famous proposal of an ethic of responsibility as a second-level normative ethical approach to ethics with responsibility as its lodestar. A case is argued that his ethic of responsibility entails a new approach to ethics at the beginning of the twentieth century that can also, in an adapted form, serve as a model at the beginning of the twenty first century. At the end of the article an exposition of my own proposal for an appropriate contemporary ethic of responsibility is given and a brief outline of a programme for the future development of such an ethic provided.